Management in Public Administration Developments and Challenges in Adaption of Management Practices Increasing Public Value - Bodemann, Markus (Sustainable Management, Wertschöpfung und Effizienz,, 2018)
In this book Markus Bodemann bridges the differences between public and private sector in aspects of management, especially risk management. A survey to draw a line between both sectors describes the current status of applied management tools and their effects. To cope with future developments, or at least to be prepared, risk management could be one tool. By using the yearly status reports the author works out the bandwidth of the impact of desired and undesired developments in public sector and the causation for more risk awareness for sustainable development in local public administration. Contents Current tendencies in business practices in public administration Today's developments of applicability of business behavior in public administration Tendencies concerning risk management practices in public administration Studies on risk management practices and risk factors in public administration Proposed framework for application of risk management practices to increase public value Target Groups Lectures and students of public sector management and risk management Professionals in management, public administration and risk manager The Author Markus Bodemann is currently a consultant for data center automation and virtualization technologies at the state data center IT.NRW in Düsseldorf. As part of the transition to the New Municipal Finance Management (NKF), he has played a key role in the content and technical implementation in public administration accounting systems.